2019
DOI: 10.1002/icd.2153
|View full text |Cite
|
Sign up to set email alerts
|

Neighbourhood chaos moderates the association of socioeconomic status and child executive functioning

Abstract: Although broad associations between socioeconomic status (SES) and child executive functions (EFs) are well established, contextual factors that may matter for effects of SES on EF are not fully understood. This study used a bioecological approach to examine factors that may moderate SES–EF relations. A socioeconomically diverse sample of children ages 4.5–5.5 completed working memory and go/no‐go tasks. Parents reported on well‐being, household chaos, and neighbourhood chaos. Higher SES related to better work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…For children aged 9–14 in the study, results suggested that high parent involvement was associated with better executive function skills, regardless of socio‐economic status. Additionally, household chaos, defined by confusion, ambient noise, clutter around the home, and neighbourhood characteristics (Matheny, Wachs, Ludwig, & Phillips, 1995; St. John & Tarullo, 2020), has been associated with executive function, through parenting behaviours (e.g., Vernon‐Feagans, Willoughby, & Garrett‐Peters, 2016). That is, a chaotic home—one in which there is more happening at a given time, less adherence to a consistent daily schedule, and a lack of routines—often predicted parenting practices that negatively impacted behaviour regulation and executive functions.…”
Section: Offering An Asset‐based Contextual Lensmentioning
confidence: 99%
“…For children aged 9–14 in the study, results suggested that high parent involvement was associated with better executive function skills, regardless of socio‐economic status. Additionally, household chaos, defined by confusion, ambient noise, clutter around the home, and neighbourhood characteristics (Matheny, Wachs, Ludwig, & Phillips, 1995; St. John & Tarullo, 2020), has been associated with executive function, through parenting behaviours (e.g., Vernon‐Feagans, Willoughby, & Garrett‐Peters, 2016). That is, a chaotic home—one in which there is more happening at a given time, less adherence to a consistent daily schedule, and a lack of routines—often predicted parenting practices that negatively impacted behaviour regulation and executive functions.…”
Section: Offering An Asset‐based Contextual Lensmentioning
confidence: 99%
“…Exposure to certain chemicals during critical windows of development causes neurotoxicity through alterations in brain structure and function and may lead to diminished cognitive development [ 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Exposures to social stressors, particularly those related to socioeconomics, have been shown to affect childhood cognitive ability in a variety of cohorts [ 7 , 27 , 28 , 29 , 30 , 31 ]. Activities, such as diet and sleep patterns, have been shown to be correlated to cognitive outcomes in children [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, this review is the most comprehensive analysis of the interactions of chemical and non-chemical stressors from the total environment on childhood cognitive development. Eleven studies published since 2016 have used Ruiz et al [ 48 ] as a springboard to examine the effects of specific stressors such as neighborhood chaos, industrial pollution, environmental contaminants, socioeconomic status, and poverty on childhood cognitive development [ 6 , 7 , 28 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. Recent publications related to childhood cognitive development that do not cite Ruiz et al [ 48 ] focus on the effects of postnatal care, maternal mental health, and physical brain characteristics [ 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…St. John and Tarullo () considered EF within the neighbourhood context among 4.5‐ to 5.5‐year‐old children. As expected, SES was associated with EF performance, but neighbourhood chaos moderated these associations.…”
Section: Other Relevant Contextsmentioning
confidence: 99%